An Extract of Zingiber officinale and Piper retrofractum Combination and Its Effect to Cancer Cell Line - Ekowati, Heny; Septiyaningsih, .; Harwoko, . (Indonesian Journal of Cancer Chemoprevention, 2011)
Chemotherapy may emerge sideeffect since it may treatinconveniently the synthesis of nucleic acids and proteins,both cancer cells or normal cells.Plants as a cancer therapy were expected to reduce this toxicityand side effects.Plants which used empirically for cancer therapy was ZingiberÃÂ  officinale cv. Rubrum and PiperÃÂ  retrofractum. This study was conducted to examine the cytotoxic activity of ethanolic extractc ombination of two plants in HeLa and T47D celllines.ZingiberÃÂ  officinale cv.Rubrum,PiperÃÂ  retro fractum and mixture (1:1)powdered then macerated with 96 % ethanol for 3x24 hours.Identification ofthe constituent that had potential anti cancer effect was usedTLC with silica GF254 as stationary phase,cytotoxic activity wasexamined by yellow MTT assay,the nanalyzed using probit.Apoptotic assay was performed by immunofluororescencemethod,using fluoro chromes ethidium bromide and acridineorange.The result showed that Zingiber officinalecv.Rubrumcontains terpenoids, while PiperÃÂ  retrofractum contains alkaloids substance. The mixture showed cytotoxic activity against HeLa and T47D cell with IC50 33 and 53 6g/mL respectively.Theextract caused cytotoxic effect through apoptotic mechanism.